Digital work, “uberization” of the labour relations and the resistances to it - Marques Alves, P. (IV International Meeting of Industrial Sociology, Sociology of Organisations and Work (ISSOW). Work, (In)equalities and Social Relations in the Digital Economy, 2021)
Robotics, artificial intelligence, algorithms, internet of things (IoT), cloud, connected factories, augmented reality, big data, additive manufacturing (AM), also known as 3D printing, industry 4.0., collaborative economy, digital work and digital platforms, among others, are terms we hear about more and more referring to the technological revolution currently underway. According to Fuchs (2014), “digital work is a specific form of work that makes use of the body, mind or machines or a combination of all or some of these elements [and it includes] a large variety of activities that create use-values that are objectified in digital media technologies, contents and products generated by applying digital media.” As in previous technological revolutions, fears of the implications of the increasing incorporation of dead work into the work process and consequent replacement of living work arise. There are also questions regarding working conditions and labour social relations. The intensification of the exploitation of the workforce and the deterioration of the working conditions are evident throughout the digital work chain, from mining to digital platforms, passing through hardware assemblage, software production, call centres or the e-commerce, not forgetting the unpaid work of the prosumers. Many authors referring to this process as the "uberization of societies". Facing to this new reality in the world of work forms of individual and collective resistance using several repertories of action have emerged, what some authors considered almost impossible. They are featured by a workforce with specific characteristics and in the context of a non-unionised sector. The Deliveroo riders strikes in the UK or their call for a consumer boycott in France; the Uber drivers strike in several countries last year or the strikes in the hardware assemblage in Asia are some examples. With this paper we intend to analyse these resistances in Portugal, mainly focusing on the call centre industry and in the digital platform work. The strikes in several call centres last years or the slow running of the TVDE drivers in the beginning of this year will be considered, not forgetting that this new situation challenges the unions whether traditional or new.